Life course and mental health: a thematic and systematic review - Zhang, Yuhu; Shaojun, Chen; Akintunde, Tosin Yinka; Okagbue, Ekene Francis; Isangha, Stanley Oloji; Musa, Taha Hussein (Frontiers in Psychology, 2024)
Objective: This study aims to explore the influence of the life course on mental health by identifying key trends, seminal works, and themes in existing research. Additionally, it highlights the major discussions at the intersection of life course and mental health Methods: Documents were extracted from the Web of Science Core Collection (WoSCC), to systematically analyze themes on mental health outcomes across the life course. The analysis was based on key bibliometric tools, including VOSviewer 1.6.11, R Studio software, and GraphPad Prism 9 to analyze the evolution and impact of scholarly contributions in this domain. Results: The accumulated body of research concerning the life course's impact on mental health, which began to emerge around 1990 displayed a consistently upward trend. Predominant contributions originate from developed nations and frequently delve into the psychosocial determinants of mental health over life course. Life course and mental health studies have been extensively infused with biopsychosocial frameworks that consider the role of genetic makeup, neurodevelopment, cognition, affect, sociocultural dynamics, and interpersonal relationships. Life course theory application in mental health highlight the substantive effects of accumulated adversities, notably social determinants of health, adverse childhood experiences (ACEs), and their implications for subsequent mental health outcomes. Conclusion: The nexus of life course and mental health outcomes demands further scholarly interrogation, particularly within underserved regions, to strengthen protective mechanisms for vulnerable populations.